Framing Russia-Ukraine War in the Newspapers of Bangladesh: A Topic Modeling Approach - Nath, Chuton Deb; Biswas, Anirudha; Sultana, Nigar; Shozal, Sish Ahemmed (South Asian Journal of Social Sciences and Humanities, 2024)
Background: Media coverage consistently exerts a significant influence on the formation of the public’s opinion, especially framing the war. Media framing refers to the deliberate selection and presentation of information in a manner that influences people’s perception and reaction to specific aspects of an issue. The major objective of this study was to investigate how Bangladeshi Print media frame the Russa-Ukraine Conflict (RUC) during the conflict period. Methods: The study comprised of scrapped data from the online version of two newspapers the Daily Star (n=1135) and New Age (n=728) news items related to the RussaUkraine conflict from 24 February 2022 to 24 February 2023. The news stories were scraped utilizing Python’s web scraping package Beautiful Soup. The data is analyzed adopting the Latent Dirichlet Allocation (LDA) topic modeling technique to determine the dominant framings like top keywords, top key phrases, and the most highlighted topic of the RussaUkraine war. Results: The frequency analysis of the Daily Star showed Ukraine (n=7,112) and Russia (n=5,884) being the most frequently used words, similarly New Age depicted Ukraine (n=4,901) and Russia (n=3,655) as both newspaper’s top two mentioned words: Ukraine and Russia, were the same. The ‘United States’ was the top and second most used key phrase in New Age and The Daily Star, correspondingly. Surprisingly, Daily Star mentioned ‘United States’ (n=487) and ‘Joe Biden’ (n=211) in a notable amount though the United States was not a direct part of the conflict. The topic analysis showed that the topic – ‘Military confrontations between Russia-Ukraine’ (frequency =513) and the topic- ‘Russia and Ukraine’s military clashes’ (frequency= 421) had the utmost priority in the coverage of the Daily Star and the New Age, respectively. Conclusion: It was evident from our findings that Unites States, Joe Biden, western, sanctions, European Union, security council, Black Sea etc. topics were got much attention in compared with the sufferings of the victims, price hike, energy crisis etc. topics.